Efficiency Assessment of Economic International Cooperation in Development of Arctic Offshore Oil and Gas Resources - P. V. Beresneva (Vestnik MGIMO-Universiteta)
The research is focused on efficiency assessment of economic cooperation in development of Arctic offshore oil and gas resources. The author developed an economic model based on cost-benefit analysis (CBA). CBA is used in some countries (EU, USA, Australia) as an analytic tool to make public policy decisions. CBA is based on the method of discounting cash flows associated with costs and benefits of public policy. It is assumed that all public goals are equally important inter alia, hence public bodies should opt for those initiatives that maximize public benefits for every dollar spent from the state budget. There are five stages of economic modeling: 1) the definition of public benefits and costs associated with the public initiative; 2) monetary valuation of costs and benefits; 3) the definition of discounting period and discounting rate; 4) the calculation of net present value of cash flows; 5) the comparison of initiatives' net present values. The model is built with a number of hypotheses assumed. It allows making evaluation of investments into the technology to decrease the cost of Arctic offshore oil and gas development. Moreover, the model has two scenarios describing a public policy to support technology development with international economic cooperation and without it. Under given hypotheses both scenarios return positive net present value of policies which proves that governmental initiative to support Arctic technology development is economically justified. Also the model sows that the scenario with international cooperation is more efficient from economic point of view. It is explained by two factors: the higher speed of technology transfer (due W international cooperation) and the opportunity to use financial leverage (attracting the funds from foreign partners). The model allows closing the existing scientific gap between the theory of CBA method and its practical use in public decision making.